Maritime Domain Awareness (MDA) and Archives: the Role of Archives in Sovereignty - Rachmaji, Achmad Syarif (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
In the pursuit of enhancing awareness and preparedness for territorial waters, Maritime Domain Awareness (MDA) is closely associated with the role of archives in upholding state sovereignty. Archives function as documentation of events and activities within an area, serving as tangible evidence of control over that region. This paper explores the connection between MDA and archives in the context of sovereignty, posing a central question: How does the role of archives contribute to maintaining sovereignty within the MDA framework? Utilizing qualitative research methods and a literature study, the paper delves into the actors responsible for creating agency, the categories, and the functions of archives in upholding sovereignty within the MDA concept. Primary sources include literature on MDA and regulations governing archives, with data analysis conducted through the stages of a literature study. The MDA concept operates as a unified system involving various actors in a given area, with information at its core – information preserved in archives. Archives within the MDA concept emerge as an alternative means of identifying actors and documenting proof of state territorial sovereignty. In the maritime field, at least 13 agencies or actors contribute to the production of archives. These accumulated archives are considered treasures, aligning with the provisions of Law Number 43 of 2009 regarding archives, labeled as guarded records. The triad of MDA, archives, and sovereignty establishes a significant link in safeguarding Indonesia’s territorial integrity. MDA archives play dual roles in sovereignty: facilitating effective occupation and soft diplomacy. They serve as tangible evidence of ownership, control, and management of maritime areas, reaffirming Indonesia’s territorial sovereignty.